Simulation Analysis of Two-Phase Heat Transfer Characteristics In a Smooth Horizontal Ammonia (R717) Evaporator Tube - Balthazar, Pravinth; Abdul Majeed, Muzathik (CFD Letters, 2021)
Ammonia is an important refrigerant in modern refrigeration industry due to zeroozone depletion potential and zero global warming potential. This paper focused on comparison of horizontal evaporators’ two-phase heat transfer coefficient characteristics and pressure drop verses the vapour qualities in a simulated ammonia evaporator refrigeration system in a virtual environment using the experimental results. In this study, two-phase ammonia fluid flow with mass fluxes from 50 to 150 kg/s.m2, vapour qualities between 0 and 0.6, heat flux 40 kW/m2 and saturation temperature -20o C were considered. Similarly, two-phase pressure drop correlation also simulated in virtual environment for mass flux 100 kg/s.m2, heat flux 70 kW/m2 and vapour qualities in between 0.1 and 1.0. Finally, the simulated results were compared with the experimental values and validated. Results were signified that 100 kg/m2 s mass flux showed experimental and simulation deviation 3.52% and 5.5% for pressure drop and two-phase heat transfer coefficient, respectively. Two-phase heat transfer coefficient increased by 75.7% when mass flux is increased from 50kg/m2 s to 100kg/ m2 s.